The Epidemiology of Blood-Contaminated Needlestick Injuries Among Veterinarians in Portugal - Mesquita, João R. (2015)
Needlestick injuries (NIs) are considered a substantial occupational health and safety hazard in contemporary health care practice. Unlike human medicine where much effort has been devoted to reduce the incidence of these events, the same aggressive approach has not been used in veterinary medicine. This study investigated the occurrence of blood-contaminated NIs in Portuguese veterinarians. Participants of a veterinary meeting were asked to complete a questionnaire-based survey. Differences in NI exposure rates by sex, years in practice, and animal interaction during childhood were evaluated using the chi-square test. Univariate and multivariate logistic regression analyses were performed to produce predicted probabilities for NI episodes in veterinarians. From the total of 373 enrolled veterinarians, 293 (78.5%) reported having had at least one NI during their professional life. Veterinarians working with dogs were more likely to have experienced a NI (adjusted odds ratio [aOR]: 145.74, P < .001). The high level of NIs observed in these professionals shows that NIs are a potential occupational health problem in Portuguese veterinarians, with the possibility for transmission of haematogenous zoonosis.